2009
DOI: 10.1590/1809-9823.2009120200
|View full text |Cite
|
Sign up to set email alerts
|

Incontinência urinária em mulheres no período pós-menopausa: um problema de saúde pública

Abstract: tossir e subir escadas. Observou-se que as mulheres com maior índice de massa corporal apresentaram maior frequência de incontinência. Conclusões: os dados deste estudo sugerem que a incontinência urinária tem prevalência importante entre as mulheres pós-menopausa e que esta condição se relaciona em parte a fatores que podem ser prevenidos, apontando para a necessidade de intervenção junto a esse estrato populacional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
15

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 9 publications
(5 reference statements)
0
5
0
15
Order By: Relevance
“…Considerando-se que as mulheres podem viver mais de um terço de suas vidas após a menopausa, surge a necessidade de serem aprofundados conhecimentos sobre o processo natural do envelhecimento feminino e, também, sobre as patologias ou afecções que podem ocorrer facilmente nessa população 4 .…”
Section: Introductionunclassified
“…Considerando-se que as mulheres podem viver mais de um terço de suas vidas após a menopausa, surge a necessidade de serem aprofundados conhecimentos sobre o processo natural do envelhecimento feminino e, também, sobre as patologias ou afecções que podem ocorrer facilmente nessa população 4 .…”
Section: Introductionunclassified
“…Therefore, the interest in researching the relation between women's health and quality of life increases, since they may live more than one third of life after menopause 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to understand the transformation due to voice change in menopause in women daily life and its relation to quality of life 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, if the steady increase in the population's life expectancy is not followed by improvements in health and quality of life (QOL), it can lead to high public expenditure. Based on this, greater attention can be paid to the management of urinary incontinence through public programs and policies that encourage health promotion and the prevention of this dysfunction 5 . Among others, UI care involves the assessment of pelvic floor muscle function (PFM), which can be conducted manually or instrumentally 6 .…”
Section: Introductionmentioning
confidence: 99%
“…As seen in the literature, physical therapy is efficient in reducing urine loss and improving pelvic floor muscle function and QOL. It can be easily carried out in Primary Health Care Units at low costs 5,17,19,24 , either in groups or individually (in the latter case, after approximately 14 treatment sessions 24 ). Taking into consideration the effectiveness of the physical therapy treatment reported in the literature 19,24 , the high prevalence of UI found among the elderly women in this sample, the connection between UI, functional decline 30 and falls in the elderly 32 and the subsequent loss of independence that affects most of the fallers 33 , it is suggested that the elderly users of the public health system should be given access to this therapeutic modality.…”
mentioning
confidence: 99%